Qualitative thematic analysis based on descriptive phenomenology - Annelie J. Sundler; Elisabeth Lindberg; Christina Nilsson; Lina Palmér (Wiley, 2019)
Abstract Aim The aim of this paper was to discuss how to understand and undertake thematic analysis based on descriptive phenomenology. Methodological principles to guide the process of analysis are offered grounded on phenomenological philosophy. This is further discussed in relation to how scientific rigour and validity can be achieved. Design This is a discursive article on thematic analysis based on descriptive phenomenology. Results This paper takes thematic analysis based on a descriptive phenomenological tradition forward and provides a useful description on how to undertake the analysis. Ontological and epistemological foundations of descriptive phenomenology are outlined. Methodological principles are explained to guide the process of analysis, as well as help to understand validity and rigour. Researchers and students in nursing and midwifery conducting qualitative research need comprehensible and valid methods to analyse the meaning of lived experiences and organize data in meaningful ways.